Female Anti-Suffragism: The Opposition to Women’s Parliamentary Franchise in England (1837-1928) - LAIDI, Zohra (My University, 2020)
Within the nineteenth century, Britain seen the rise of the female Suffrage Development. In 1866, these ladies suffragists’ point was the parliamentary emancipation of women. In 1899, the appearance of the Female Anti-Suffrage Movement was organized to contradict the give of the parliamentary establishment for women. This research work pursues to highlight the reasons that pushed women to restrict the parliamentary franchise for women. The antis had a surfeit of contentions which defended their cause which was the resentment of the political equality between men and women. In 1918, the Female against Suffrage Campaign was defeated. The partial enfranchisement was given to women over the age of thirty. A decade after and with the Equal Enfranchisement Act (1928), all women at last accomplished the same voting rights as men.
Keywords: Female Suffrage; Suffragists; Women; Anti-Suffrage; Parliamentary Franchise; Political Equality